CD73 contributes to anti‐inflammatory properties of afferent lymphatic endothelial cells in humans and mice. Issue 1 (29th October 2020) - Eichin, Dominik; Pessia, Alberto; Takeda, Akira; Laakkonen, Joni; Bellmann, Lydia; Kankainen, Matti; Imhof, Beat A.; Stoitzner, Patrizia; Tang, Jing; Salmi, Marko; Jalkanen, Sirpa
Abstract: CD73 is an important ectoenzyme responsible for the production of extracellular adenosine. It is involved in regulating inflammatory responses and cell migration and is overexpressed in various cancers. The functions of CD73 in blood endothelial cells are understood in detail, but its role on afferent lymphatics remains unknown. Moreover, anti‐CD73 antibodies are now used in multiple clinical cancer trials, but their effects on different endothelial cell types have not been studied. This study reveals that a previously unknown role of CD73 on afferent lymphatics is to dampen immune responses. Knocking it out or suppressing it by siRNA leads to the upregulation of inflammation‐associated genes on lymphatic endothelial cells and a more pro‐inflammatory phenotype of interacting dendritic cells in vitro and in vivo. In striking contrast, anti‐CD73 antibodies had only negligible effects on the gene expression of lymphatic‐ and blood‐endothelial cells. Our data thus reveal new functions of lymphatic CD73 and indicate a low likelihood of endothelial cell–related adverse effects by CD73 targeting therapeutic antibodies. Abstract : Silencing CD73 increases the expression of MHCI and ICAM‐1 on lymphatic endothelial cells (LECs), resulting in elevated MHCII and CD83 levels on DCs. This is also the case for inflammatory genes such as TGFB1 or CD69. In contrast, modulating CD73 expression with antibodies showed no such effect with LECs or blood endothelial cells.